Study of heart disease in pregnancy and its effect on maternal outcome - Jain, Nitin Kumar; Sultan, Shabana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Heart diseases in pregnant women and has higher incidence of maternal mortality and morbidity and is regarded as risk factor for unfavourable outcome of pregnancy both for the mother and the foetus. Heart disease in pregnancy was found to be second indirect cause contributing to maternal mortality in India. Methods: This study is a hospital based prospective analytical study carried out in the Department of Obstetrics and Gynaecology, Sultania Zanana Hospital, Gandhi Medical College, Bhopal over a period of 1 year from 1st March 2017 to 28th February 2018. Patients were evaluated clinically by both obstetrician and cardiologist and followed all through their hospital stay till discharge. Results: Total 51 cases of heart disease were found during the study period. Incidence of heart disease in our study during study period was found 0.25%. Most patients were unbooked 33(64.71%) and maximum number of patients belonged to NYHA functional class II 24 (47.06%), RHD cases were 4 times more common than CHD. 24 (47.06%) patients had undergone surgical intervention for heart disease. Congestive cardiac failure was most common complication seen. Three maternal deaths were seen. All cases belonged to NYHA functional class III. All 3 cases were unbooked presented first time in labor. Conclusions: We found that pregnancy outcome was good in booked cases with regular checkup by obstetrician and cardiologist, surgically corrected cases and those with NYHA functional class I and II. Hence, joint management by obstetrician, cardiologist, and anesthetist is required to ensure better maternal outcome.